Vitalisasi Pembangunan Jemaat: Model Lima Faktor dalam Konteks Gereja yang Cair sebagai Dasar Mencapai Visi HKBP - Oking Sahrul Silitonga; Azwar Anas Pasaribu (STT HKBP Pematangsiantar, 2024)
This paper examines Jan Hendriks' five-factor model for congregational revitalization, integrating it with Pete Ward's Liquid Church theory to address contemporary challenges in church development. Congregational revitalization, characterized by both internal fortification and external engagement, is crucial for realizing an effective and sustainable ecclesial vision. Hendriks' model emphasizes five key dimensions: climate, leadership, structure, goals and tasks, and identity. By incorporating Ward's Liquid Church theory, this approach introduces the adaptability required to navigate evolving sociocultural contexts without compromising the core ecclesial identity. In this framework, the paper highlights the critical role of shared leadership in cultivating dynamic, empowered, and relevant congregations.